Assessing biogeochemical controls on porewater dissolved inorganic carbon cycling in the gas hydrate-bearing sediments of the Makran accretionary wedge, Northeastern Arabian Sea off Pakistan - Chen, Yuanqing; Xu, Sinan; Liu, Weining; Zhang, Zhen; Yang, Tianbang; Xiao, Xiao; Deng, Xiguang; Li, Jiangtao; Yao, Huiqiang; Wu, Zijun (Frontiers in Marine Science, 2024)
Quantitatively assessing the porewater dissolved inorganic carbon (DIC) cycling in methaneenriched marine sediments is crucial to understanding the contributions of different carbon sources to the global marine carbon pool. In this study, Makran accretionary wedge was divided into Zone 1 (high methane flux area) and Zone 2 (background area). Porewater geochemical compositions (Cl -, SO4 2-, NH4 + , Mg 2+ , Ca 2+ , DIC and δ 13 C-DIC) and a reaction-transport model were used to determine the DIC source and calculate the DIC flux through carbonate precipitation and releasing into overlying seawater in the gas hydrate-bearing sediments. Zone 1 is characterized by the shallower depth of sulfate-methane transition (SMT), where most of porewater sulfate was consumed by anaerobic oxidation of methane (AOM). In contrast, a relatively low flux of methane diffusion in Zone 2 results in a deeper SMT depth and shallow sulfate is predominantly consumed by organoclastic sulfate reduction (OSR). Based on the porewater geochemical profiles and δ 13 C mass balance, the proportions of porewater DIC originating from methane were calculated as 51 % in Zone 1 and nearly 0 % in Zone 2. An increase of porewater DIC concentration leads to authigenic carbonate precipitation. Solid total inorganic carbon (TIC), X-ray diffractometry (XRD) and scanning electron microscopy (SEM) analysis display that carbonate content increases with depth and aragonite appears at or below the depths of SMT. Meanwhile, the flux of DIC released from sediments calculated by the reaction-transport model is 51.3 ~ 90.4 mmol/m 2 •yr in Zone 1, which is significantly higher than that in Zone 2 (22.4 mmol/m 2 •yr). This study demonstrates that AOM serves as the dominant biogeochemical process regulating the porewater DIC cycle, which has an important impact on the authigenic carbonate burial and the seawater carbonate chemistry.